2020
DOI: 10.1155/2020/1929143
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Informed Family Planning Perceptions and Decision-Making in Rural Chiapas, Mexico: A Mixed-Methods Study

Abstract: Compared to other Mexican states, Chiapas possessed the lowest rate of contraception use among women 15−49 years old (44.6%) in 2018. This convergent mixed-methods study assessed family planning use, perceptions, and decision-making processes among women and men in rural communities where Compañeros En Salud (CES) works in Chiapas, Mexico. We conducted surveys of reproductive-aged women and semi-structured interviews with reproductive-aged women, men, and physicians completing their social-service year in CES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Previous research findings have documented that male partners object to women using contraceptives. 25 , 26 This control is worse for the adolescent women who are more vulnerable to coercion. These findings call for renewed focus on empowering adolescent women to take charge of their fertility intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research findings have documented that male partners object to women using contraceptives. 25 , 26 This control is worse for the adolescent women who are more vulnerable to coercion. These findings call for renewed focus on empowering adolescent women to take charge of their fertility intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Decision-making processes between husbands and wives are not straight forward and determined by continuous changes in attitudes and situations ( Downey et al., 2017 ). Male partners often make the final decision about contraceptive use ( Truong et al., 2020 ). In Nigeria, for example, wives with lower socioeconomic status are less empowered to overtly use contraceptives when their husbands oppose family planning; however, they still use it covertly ( Adanikin et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, for example, wives with lower socioeconomic status are less empowered to overtly use contraceptives when their husbands oppose family planning; however, they still use it covertly ( Adanikin et al., 2019 ). Recent literature reported that both the influence of male partners and lack of women's autonomy were the main reasons for not using any MFPM ( Truong et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations